MANAJEMEN PERENCANAAN PERILAKU HIDUP BERSIH DAN SEHAT DI LINGKUNGAN RW O5 KELURAHAN MEKARJAYA - Purnamasari, Sulfi; Rahmanita, Fika; Hamda, Fitra Jaya Nasmal; Retnawati, Saptina (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Clean and healthy life behavior is a habit of community behavior in daily life as one of the efforts to prevent various cases of the spread of disease in the community life. For example cases of dengue fever which experienced a pretty drastic surge in the city of Depok, where from 75 cases of dengue fever on January 1, 2019 increased to 506 patients with dengue fever in the period January 1-31, 2019. The purpose of doing community service in RW 05 Mekarjaya sub-district Sukmajaya District Depok City is to provide understanding to the community members about the importance of making a clean and healthy lifestyle management plan in order to improve the level of public health. The method used in in community service activities uses a survey method by looking at some samples and phenomena that occur in RW 05 environment. From the analysis it is known that there asre still some clean and healthy living behaviors that have not been applied from the ten indicators used as benchmarks. Besides that there is still a lack of awareness of the community members about the importance of applying clean and healthy living behaviors in daily life in the community.